Catechol O-methyltransferase mRNA expression in human and rat brain: evidence for a role in cortical neuronal function - Matsumoto, M.; Weickert, C.Shannon; Akil, M.; Lipska, B.K.; Hyde, T.M.; Herman, M.M.; Kleinman, J.E.; Weinberger, D.R. (Neuroscience, 2003)
Catechol O-methyltransferase (COMT) is involved in the inactivation of catecholamines, including the neurotransmitter dopamine. A Val 108/158 Met functional polymorphism of the COMT gene has been shown to affect working memory-associated frontal lobe function in humans. In the present study, in situ hybridization histochemistry was employed to determine the mRNA expression profile of COMT in the human prefrontal cortex, striatum and midbrain and in the rat forebrain. In both species, COMT mRNA signals were observed in large pyramidal and smaller neurons in all cortical layers of the prefrontal cortex as well as in medium and large neurons in the striatum. Levels of COMT mRNA were obviously higher in neurons than in glia. The striatum, which receives a dense dopaminergic input, expressed lower levels of COMT mRNA as compared with the prefrontal cortex. Consistent with previous protein expression data, COMT mRNA was abundant in ependymal cells lining the cerebral ventricles. In the midbrain, COMT mRNA was detected in dopaminergic neurons in both species, albeit at low levels. In the rat forebrain, dense labeling was also detected in choroid plexus and hippocampal dentate gyrus and Ammon’s horn neurons. Contrary to expectations that COMT would be expressed predominantly in non-neuronal cells, the present study shows that neurons are the main cell populations expressing COMT mRNA in the prefrontal cortex and striatum. Combined with previous data about protein localization, the present results suggest that the membrane-bound isoform of COMT having a high affinity for dopamine is expressed at neuronal dendritic processes in human cortex, consistent with functional evidence that it plays an important role in dopaminergic neurotransmission. Published by Elsevier Science Ltd on behalf of IBRO.